Proposals that work a guide for planning dissertations and grant proposals - Locke, Lawrence F.; Spirduso, Wareen Wyrick; Silverman, Stephen J. (Thousand Oaks, California SAGE, 2014)
Previous editions of this book have helped well over 100,000 students and professionals write effective proposals for dissertations and grants. Covering all aspects of the proposal process, from the most basic questions about form and style to the task of seeking funding, Proposals That Work offers clear advice backed up with excellent examples. Ináthe fifth edition, the authors haveáincluded a discussion of the effects of new technologies and the Internet on the proposal process, with URLs listed where appropriate. In addition, there are new sections covering alternative forms of proposals and dissertations and the role of academic rigor in research. As always, the authors have included a number of specimen proposals, two that are completely new to this edition, to help shed light on the important issues surrounding the writing of proposals. Clear, straightforward, and reader friendly, Proposals That Work is a must own for anyone considering writing a proposal for a thesis, a dissertation, or a grant.
Part I. Writing the proposal -- The function of the proposal -- Doing the right thing : "the habit of truth" -- Developing the thesis or dissertation proposal : some common problems -- Content of the proposal : important considerations -- Preparation of proposals for qualitative research : different assumptions -- Proposals for mixed method research -- Style and form in writing the proposal -- The oral presentation -- Part II. Money for research -- Money for research : how to ask for help -- Preparation of the grant proposal -- Part III. Specimen proposals -- Proposal 1: Experimental study: The effects of primate vocalizations, backward speech, and filtered speech on object categorization during the first year -- Proposal 2: Qualitative study: An advisory team for social justice education : teachers' and the principal's perceptions on four key dimensions of the ninth grade advisory program -- Proposal 3: Online electronic survey study: The nutrition care process of front-line pediatric HIV providers -- Proposal 4: Funded grant: How higher education in prison affects student-inmates' social capital and conceptions of self -- Appendix: Annotated bibliography of supplementary references
Keywords: Proposal writing in research -- Handbooks, manuals, etc; Dissertations, Academic -- Handbooks, manuals, etc; Research grants -- Handbooks, manuals, etc; Fund raising -- Handbooks, manuals, etc